Criminal Law Enforcement on Domestic Violence Offenses Involving Religious Leader: A Juridical Analysis - Angeliq Yuan Pratiwi; Sinarianda Kurnia H. (Fakultas Hukum Universitas Bhayangkara Surabaya, 2026)
This study examines the legal suitability of Restorative Justice (RJ) as a resolution mechanism for domestic violence cases committed by religious leaders, drawing on the case of pastor Hendryanto Udjari or Moses Henry in Surabaya, East Java. Employing a normative juridical method through statutory, case, and conceptual approaches, the analysis is grounded in Satjipto Rahardjo's law enforcement theory, John Rawls' substantive justice theory, and criminal liability theory. The study identifies layered enforcement barriers, including evidentiary difficulties arising from the hidden nature of domestic violence, religious community intervention pressuring victims into reconciliation, and inadequate institutional protection against revictimization. The findings indicate that domestic violence perpetrated by religious leaders is unsuitable for resolution through RJ, as the deeply asymmetric power relationship between perpetrator and victim risks reducing the mechanism into an instrument of social coercion and concealed impunity. Where RJ is nonetheless considered, its application can only be legally justified when cumulative preconditions are satisfied, including the victim's free and informed consent, genuine acknowledgment of wrongdoing by the perpetrator, an independent facilitator, and rigorous oversight, while maintaining RJ strictly as a complementary mechanism rather than a substitute for formal criminal proceedings. This study recommends consistent law enforcement grounded in the principle of equality before the law and substantive justice, irrespective of the perpetrator's social standing.